Dynamics of identity in the world of the early Christians associations, Judeans, and cultural minorities - Harland, Philip A. (New York : T & T Clark, 2009)
This study sheds new light on identity formation and maintenance in the world of the early Christians by drawing on neglected archaeological and epigraphic evidence concerning associations and immigrant groups and by incorporating insights from the social sciences. The study's unique contribution relates, in part, to its interdisciplinary character, standing at the intersection of Christian Origins, Jewish Studies, Classical Studies, and the Social Sciences.  It also breaks new ground in its thoroughly comparative framework, giving the Greek and Roman evidence its due, not as mere ba
Introduction -- pt. 1: Judean and Christian identities in the context of associations -- Associations and group identity among Judeans and Christians -- Local cultural life and Christian identity : "Christ-bearers" and "fellow-initiates" -- pt. 2: Familial dimensions of group identity -- "Brothers" in associations and congregations -- "Mothers" and "fathers" in associations and synagogues -- pt. 3: Identity and acculturation among Judeans and other ethnic associations -- Other diasporas : immigrants, ethnic identities, and acculturation -- Interaction and integration : Judean families and guilds at Hierapolis -- pt. 4: Group interactions and rivalries -- Group rivalries and multiple identities : associations at Sardis and Smyrna -- Perceptions of cultural minorities : anti-associations and their banquets.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Identification (Religion); Church history -- Primitive and early church, ca. 30-600.; Christianity and other religions; Religions -- Relations; Religion; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Judentum; 2; Christentum; Familie; 2; 2; 2; Akkulturation; Juden; Geschichte 30-500; Electronic books